(untitled) (Global Journal of Human-Social Science, 2016)
Introduction-The inferior quality of education that African American children receive leads to perpetual economic inequality and lack of political power to change it. There is a dimension of European colonialism in the American educational ethos. The non-recognition of the culture of African American children in main stream psychology and education practice constitutes ethnocentrism. African American culture is overridden, ostensibly to impart efficient "mainstream" education. But the process creates alienation and disconnection from the school and academic pursuits for many African American learners. The goal is to impart the same excellent out comes to all children but to find away to do it within the context of their culture and learning styles. The task for urban educators is to describe the achievement gap; delineate the causes of the achievement gap; and develop strategies to eliminate the achievement gap. Urban educators are called upon to address the dynamic character of urban life offering pedagogy that is sensitive to the special experiences, conditions and opportunities presented by a culturally diverse student body. Urban education calls for a commitment to excellence in education, inclusion and social justice..